Exploration of risky riding behaviour among young motorcyclist - Siti Zun Nurain, Mohd Ali; Intan Suhana, Mohd Razelan (IOP Publishing, 2021)
Road traffic crashes appears to be an endless problem (Kareem A 2003). Nowadays, statistics by Department of Road Transport showed that the road traffic crashes are significantly increasing in Malaysia every year. According to Royal Malaysian Police (PDRM) report, motorcyclists are more prone to crash when they are on the road compared to drivers of other vehicles. There are many factors that contribute to the road traffic crashes in young motorcyclists such an inexperience, lack of riding skill and risk riding behaviour that have been related to the collisions in which motorcycles have been the most popular choice of vehicles among young motorcyclist. This research evaluates the correlation between the set of risky riding behaviour among secondary school students based on their background. To prove that risk behaviours majorly contributed to the number of motorcycle crashes, determination of risky riding behaviour within secondary school student at schools' compound were conducted. Data collection also were collected through questionnaire distributed through google form for school students and young motorcyclist to assess their level of contribution in risky riding behaviour. The findings proved that, breaking the speed limit are the most popular risky riding behaviour among the school children. Meanwhile, riding while impaired and performing stunting acts are the behaviours considered to be less contributed to the number of motorcycle crashes. Correlation result shows that neglection of speed limit was highly contributed to the motorcycle crashes among the secondary school student. This result is very useful for the enforcement bodies to strategize their effort in curbing the crash issues involving young riders.